Historical changes of bottom topography and tidal amplitude in the Ria de Aveiro, Portugal: trends for future evolution - Silva, J. F. (2015)
The natural evolution of the estuary-coastal lagoon system of the Ria de Aveiro, Portugal, was halted in 1808 by the construction of a new inlet/outlet channel through the sand spit which isolates it from the Atlantic Ocean. In consequence, tidal amplitudes in the lagoon increased from 0.07–0.13 m to over 1 m. Improvements to the channel since 1936, including construction of jetties, breakwaters and dredging, have increased its cross-sectional area. This has caused a steady increase in tidal amplitude to between 2.5 and 2.8 m, the erosion of mud flats, salt marsh and old salt pans, the widening and deepening of channels, and a greater capacity for sediment transport and dispersal due to the increased tidal currents. The volume of the tidal prism calculated for spring tides is now 1.7 times that in 1951; thus areas bordering the lagoon, especially agricultural fields, are experiencing a progressively increasing risk of flooding and salt water contamination at high water. Any future increase of mean sea level will contribute to an increase of both area and volume of the water mass and could cause important changes to the dynamics of the system. An increase in mean sea level of 0.1 m will, for example, correspond to an increase of 5% in the capacity of the system and contribute to an increase in the speed of tidal propagation. The resulting increase in the volume of the tidal prism will be up to 22% of the present maximum value.